Market choice and technology intensity of exports in international business networks: Firm-level evidence from Poland - Andrzej Cieślik; Jan Jakub Michałek; Krzysztof Szczygielski (Entrepreneurial Business and Economics Review (EBER), 2024)
Objective: The objective of the article is to study links between market choice and technology intensity of exports in international business networks for firms located in Poland during the 2016-2020 period. Research Design & Methods: We analysed the decisions of firms to sell in one or more geographical markets (national, European, non-European) using the Community Innovation Survey of Polish manufacturing and services firms. We singled out firms that are subsidiaries of multinational enterprises originating from large developed economies including the US, Germany, UK, and France, and compared their market choices to those of indigenous firms. Findings: The results show that membership in international business networks increases the probability of exporting. However, the effects differ by the parent company's country of origin. The increase in the probability of EEA+ market presence is especially high in the case of German and British business groups and less pronounced in the case of American and French groups. On the other hand, membership in the American, French, and other business groups increases the probability of selling to non-EEA+ markets. The role of foreign business groups depends on the technology intensity of the industry in which they operate. German subsidiaries are the most likely to export if they are active in the high-tech, medium-low-tech, and low-tech manufacturing sectors. For French subsidiaries, it is in the medium-high-tech and high-tech manufacturing sectors. High-tech services are likely to be exported by members of foreign business groups regardless of the origin of the parent company. Implications & Recommendations: Our study showed the essential role of European integration for exports of firms based in Poland. It also showed that the risk of technologically stagnant 'East' - 'West' networks, similar to Mexican maquilladora, based mainly on the low cost of labour, did not materialize. Contribution & Value Added: The work is original as it uses a unique Polish CIS firm-level dataset that allows for distinguishing between market choices of foreign-owned and indigenous firms located in Poland.
Keywords: F12; F14; F23; L25; O31; 330; exporting; international business networks; market choice; technology intensity; Poland